ANALYSIS OF THE SOCIAL IMPACT OF GRANITE MINING ACTIVITIES ON THE SURROUNDING COMMUNITY - Lismei Sihombing (RADJA PUBLIKA, 2026)
Granite mining activities contribute to regional economic growth by creating job opportunities, boosting community income, and fostering infrastructure development. However, these activities also carry the potential for various social impacts that effect the living conditions of communities surrounding the mining areas. This study aims to analysis the social impacts of granite mining from a sustainable development perspective by examining social, economic, and community well-being aspects. A descriptive methode with a qualitative approach was employed. Data collection involved field observations, interviews, and a review of documents. The findings indicate that granite mining generates positive impacts, such as increased employment opportunities, higher community income, the growth of local businesses, and improved access to infrastructure. Conversely, the community also experiences negative impacts, including shifts in livelihood patterns, potential social conflict, disturbance caused by dust and noise, and environmental degradation that affects social activities. The study concludes that granite mining entails multidimensional social impacts both positive and negative. Therefore, synergy among the company, the government, and the community is essential to achieve sustainable mining management, ensuring that economic benefits go hand-in-hand with improved social well-being and environmental preservation